Pengaruh literasi keuangan, literasi digital, digital marketing, brand image dan word of mouth terhadap minat generasi z pada bank syariah - Dafiq, Bahru Ilmi; Hidayati, Amalia Nuril; Habib, Muhammad Alhada Fuadilah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the influence of financial literacy, digital literacy, digital marketing, brand image and word of mouth on the interest of Generation Z in Islamic banks (a case study in Wonorejo village). Researchers used primary data obtained from distributing questionnaires to students in Wonorejo Village, Sumbergempol District, Tulungagung Regency with a total sample of 94 respondents. The research method is data analysis using a descriptive approach and PLS analysis techniques with the help of the Smart PLS version 3.0 application. The results of this study indicate that financial literacy, digital literacy and word of mouth have a significant influence on the interest of generation z to use Islamic banks.